The Effect of Effleurage Massage on the Level of Back Pain Scale in Trimester III Pregnant Women - Ade Marlisa Rahmadayanti; Titin Apriyani; Yan Permadi (Lentera Perawat, 2024)
Pregnancy is a physiological process that occurs in every woman in the reproductive phase. The growth and development of the fetus in the uterus can result in anatomical and physiological changes in pregnant women. The occurrence of back pain is caused by musculoskeletal changes. By providing massage therapy it is hoped that it can reduce the severity of back pain in third trimester pregnant women. This research used a pre-experimental design with a pretest-posttest with control group design. The sampling method used a purposive sampling technique, which took samples from third trimester pregnant women who experienced back pain in the Lubuk Bintialo Health Center Work Area. Data analysis used in this research was the T-test to determine the effect of effleurage massage on the level of the back pain scale. Based on research conducted, of the 18 respondents before receiving effleurage massage in the treatment group, the average maternal pain scale was 5.44, while in the control group it was 5.67. Meanwhile, after receiving effleurage massage, the treatment group experienced a significant decrease with a mean of 3.7 with a mean difference of 1.66 before being given effleurage massage. Meanwhile, in the control group, the average result was 5.56 with a mean difference of 0.11. The results of bivariate analysis using the T-test obtained sig results. 0.000 < 0.05 indicates that there is an influence of effleurage massage on the back pain scale level of pregnant women in the third trimester. Thus, the application of effleurage massage can be used as an alternative treatment to reduce back pain in third trimester pregnant women by doing it according to the procedure.